Contrastive Analysis of Metaphorical Means of Representation of the Concept “Fear” in the Novel by G. Muller “Herztier” and its Translation into the Russian Language - Bulatova, Alsu (Journal of History Culture and Art Research, 2018)
This article studies metaphorical expressions, as well as comparative phrases that represent the emotional state of fear. The material of the study was the novel by German writer Gerta Müller “Herztier” and its translation into the Russian language. It is worth mentioning that this investigation is not only congruent with the system-structural approach but also with the system of cognitive approach to language. In the novel by Gerta Müller “Herztier”, which we analyze, and its translation into Russian, figurative devices, that is, metaphorical expressions and comparisons are used to nominate the emotional state of fear. The factual analysis has shown that the so-called anthropomorphic metaphors demonstrate a greater frequency of use. Fear is personified and acquires physical characteristics peculiar to man. We have disclosed verbal zoomorphic metaphors in which the characterization of the emotional state of fear is represented through comparing with the image of an animal. In addition to metaphors, of special interest are the comparisons which are formed by adding an insertion word. We have analyzed the syntactic structure of the formation of comparisons in German and Russian, namely: Субъект (Subject)+ глагол (Verb)+ объект сравнения (Comparing Object)/ Präposition + Subjekt + (Präposition) Objekt; Субъект (Subject) + глагол (Verb) + как (like) + объект сравнения (Comparing Object) / Subjekt + Verb; Субъект + прилагательное / Adjektiv + Subjekt. The result of complex analysis reveals that a more emotionally vivid description of the emotional state of fear is observed in the Russian translation, while in the original text the author’s language is less metaphorical and the emotion is expressed less expressively.